2012
DOI: 10.1111/j.1440-1797.2012.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis, treatment with steroid and impact on renal outcomes

Abstract: StG patients had a greater degree of improvement in renal function, but with no correlation between degree of improvement in eGFR and delay in starting steroids, and similar eGFR values at final follow-up. PPI were the second commonest drug category among drug-induced cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
(31 reference statements)
1
17
0
1
Order By: Relevance
“…In a study of 187 patients with AIN (25% with drug-induced AIN, 48% with "unknown" cause), corticosteroid-treated patients had better kidney function at 2 years and lower dialysis dependence compared with those who did not receive these drugs (3). Similar outcomes were observed in other studies (4)(5)(6). Early identification of drug-induced AIN and treatment with corticosteroids were associated with better kidney function and lower need for dialysis in some studies (4,6).…”
supporting
confidence: 64%
“…In a study of 187 patients with AIN (25% with drug-induced AIN, 48% with "unknown" cause), corticosteroid-treated patients had better kidney function at 2 years and lower dialysis dependence compared with those who did not receive these drugs (3). Similar outcomes were observed in other studies (4)(5)(6). Early identification of drug-induced AIN and treatment with corticosteroids were associated with better kidney function and lower need for dialysis in some studies (4,6).…”
supporting
confidence: 64%
“…Most patients with ATIN in these studies were treated with steroids (59 – 87%), and different criteria were applied to evaluate renal recovery in each article. Three of these studies [12, 13, 16] showed that steroids were effective in renal outcome, while the other three [11, 14, 15] did not. Among the studies that analyzed the effect of steroids on drug-induced ATIN, only one study [12] showed a positive result of steroid use.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated that time to starting steroid treatment was important; those who completely recovered renal function started steroids at an earlier time point than those who had incomplete recovery. A more recent series by Raza et al [28] reports 49 patients with AIN, 37 of whom were treated with steroids. They report a greater improvement in eGFR in patients treated with steroids; mean improvement in eGFR was 3.4-fold in the steroid-treated group compared with 2.0-fold in the untreated group.…”
Section: Discussionmentioning
confidence: 99%